Nutritional value of fatty acids of the Neotropical freshwater fishes Prochilodus magdalenae, Pseudoplatystoma magdaleniatum and Ageneiosus pardalis (2020)
ABSTRACT: This study aimed to determine the nutritional value of the fatty acids in the freshwater fish Prochilodus magdalenae, Pseudoplatystoma magdaleniatum and Ageneiosus pardalis during dry and wet Neotropical seasons with the view to generate useful information for nutrition and sustainable commercial exploitation. The analysis of fatty acids was performed by gas chromatography–mass spectrometry and the nutritional value was calculated using five estimators: n-6/n-3 ratio, unsaturation index (UI), atherogenicity index (AI), thrombogenicity index (TI) and ratio of hypocholesterolemic/hypercholesterolemic (h/H) fatty acids. A different number of fatty acids (P. magdaleniatum = 50, P. magdalenae = 41, and A. pardalis = 32) was identified for each species and the average abundance percentages were different in the two seasons (p < 0.05). Prochilodus magdalenae and P. magdaleniatum showed healthy n-6/n-3 ratios (1.04 and 2.72) in the different seasons. Although the three species showed low values of UI (0.37–0.63), the remaining nutritional indexes were within the healthy range (AI: 0.04–0.70, TI: 0.66–1.07, h/H: 0.80 – 24.40). Multivariate analysis showed similar healthy nutritional values for the species, with exception of P. magdaleniatum.